Indoor Environment and Health - Korhan, Orhan (IntechOpen, 2019)
A shelter is one of the physiological needs according to Maslow's Hierarchy of Needs, which lies at the bottom of the pyramid. People spend around 90% of their time in shelters, or in today's words: buildings. They sleep, eat, work, relax, exercise, play, are born, and die in these buildings. In fact, they "live" within walls. Therefore, an indoor environment is crucial for their health and safety. This book, therefore, addresses the issues related to the impact of a sustainable healthy and comfortable indoor environment on the quality of life, and perceives the required indoor conditions for productivity and effectiveness. Thereby, this book is designed to include issues and extensive discussions on thermal comfort, indoor air quality, visual comfort, acoustic comfort, productivity, and indoor health and safety. The concepts of heating, ventilation, air conditioning, external temperature, air pollution, sick building, indoor pollutants, illumination, glare, indoor lighting, daylight, noise, construction materials, sound intensity, and furniture on the indoor environment are described in detail in this book.